2006
DOI: 10.1111/j.1574-6968.2005.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of different soil bacteria to arbuscular mycorrhizal fungal extraradical hyphae is determined by hyphal vitality and fungal species

Abstract: Attachment of certain bacteria to living arbuscular mycorrhizal fungal extraradical hyphae may be an important prerequisite for interactions between these microorganisms, with implications for nutrient supply and plant health. The attachment of five different strains of gfp-tagged soil bacteria (Paenibacillus brasilensis PB177 (pnf8), Bacillus cereus VA1 (pnf8), Pseudomonas fluorescens SBW25 :: gfp/lux, Arthrobacter chlorophenolicus A6G, and Paenibacillus peoriae BD62 (pnf8)) to vital and nonvital extraradical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
147
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(169 citation statements)
references
References 28 publications
7
147
0
6
Order By: Relevance
“…Vitality of the hyphae might also have had a role. Toljander et al (2006) found the same B. cereus strain to preferentially attach to nonvital hyphae of G. intraradices. In addition to B. cereus, also Paenibacillus spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vitality of the hyphae might also have had a role. Toljander et al (2006) found the same B. cereus strain to preferentially attach to nonvital hyphae of G. intraradices. In addition to B. cereus, also Paenibacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have investigated the ability of bacteria to attach to AMF hyphae, but only using pure and single cultures and sometimes with hyphae that were not connected to plant roots (Bianciotto et al, 1996(Bianciotto et al, , 2001Toljander et al, 2006). Such studies may therefore have been biased towards less active AMF hyphae and non-competitive attachment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta interacción son establecidas durante todas la etapas del ciclo de vida de las micorrizas, desde la formación de esporas, germinación, colonización dentro de las raíces de las planta hasta la emisión de las hifas externas (2). Los estudios taxonómicos de HMA, tradicionalmente fueron basados en la morfología y apariencia de las esporas.…”
Section: Introductionunclassified
“…Xavier and Germida (2003) reported that the spore associated bacteria of Glomus clarum may specifically stimulate spore germination. Although the fungi and its close proximity of bacteria interaction seem logical, little is known about the extent that which bacteria associate with which AMF and their specificity for interaction (Toljander et al, 2005). Scientists have identified and isolated spore associated bacteria from spore surface, inside spore, and around hyphae.…”
Section: Spore Associated Bacteria (Sab)mentioning
confidence: 99%